Analysis of the Influence of Price and Product on Purchasing Decisions Mediated by Brand Image at Maybank Indonesia Finance Lampung Branch - Oktariansyah; Budi Haryono; Soegeng Wahyoedi (Nomico, 2024)
Maybank Indonesia Finance is a financing company operating in Indonesia. In this research, there are various factors that can underlie consumer purchasing decisions. Researchers will focus on price, product and brand image as factors that can encourage consumer purchasing decisions. The existence of these various factors made researchers interested in conducting research entitled "Price and Product Analysis of Purchasing Decisions Mediated by Brand Image at Maybank Indonesia Finance Lampung Branch" as the title of this research. This type of research is causal research because it is research that looks for relationships - effects (causal relationships). The population in this research is all Maybank Indonesia Finance customers. In this research, the samples that will be taken are Maybank Indonesia Finance customers at the Bandar Lampung branch. The minimum sample size is 135 samples. Data was collected using a questionnaire, and analysis was carried out using Linear Regression and Path Analysis.  From the research findings, the four variables namely price, product, brand image, and purchase decision, are within the "good" range. This indicates that these factors are perceived positively by Maybank Finance customers in Bandar Lampung. The analysis also shows that there is an influence among these variables, both partially and through mediation, affirming the importance of interrelated relationships among them. Therefore, it is recommended for the company to pay attention to good pricing policies, design products that meet consumer needs, and develop a strong brand image to drive consumer purchase decisions for Maybank Finance Indonesia products.